Labor Market Regulations What Do We Know about Their Impacts in Developing Countries? - Betcherman, Gordon (The World Bank, 2014)
Labor market regulation is a high-profile, and often contentious, area of public policy. Although these regulations have been studied most extensively in developed countries, there is a growing body of literature on their effects in developing countries. This paper reviews that literature and focuses on the impacts of two important types of labor market regulation, minimum wages and employment protection legislation (EPL), on employment, earnings, and productivity. Strong and opposing views exist regarding the costs and benefits of these regulations, but the results of this review suggest that their impacts are generally smaller than the heat of the debates would suggest. Efficiency effects are found sometimes, but not always, and the effects can be in either direction and are usually modest. The distributional impacts of both minimum wage and employment protection legislation are clearer, with two effects predominating: an equalizing effect among covered workers, but with groups such as youth, women, and the less skilled disproportionately outside the coverage and its benefits. Although the overall conclusion is one of modest effects in most cases, the policy implication is not that these regulations do not matter. On the one hand, both minimum wages and EPL can affect distributional objectives. On the other hand, these regulations can generate undesirable economic or social impacts if they are established or operate in ways that exacerbate the labor market imperfections that they were designed to address